HBEC2703: Science in Early Childhood Education - study guide - Badzis, Mastura (Open University Malaysia (OUM), 2012)
This course is designed to provide theoretical and practical knowledge for teaching science in early childhood contexts. Learners will develop teaching strategies which promote thinking and problem-solving skills in young children; utilize observation and task assessment as a basic for planning discovery experiences for the children and select as well as prepare developmentally appropriate materials to support the learning scientific concepts.